A review: antimicrobial activity and toxicity analysis of the peel of banana, pomegranate, papaya, and citrus fruits (lemon and orange) - Suzita Ramli (Tanjung Malim, 2021)
A review: antimicrobial activity and toxicity analysis of the peel of banana, pomegranate, papaya, and citrus fruits (lemon and orange) by Suzita Ramli